VDAC2 and aldolase A identified as membrane proteins of K562 cells with increased expression under iron deprivation - Valis, Karel; Neubauerova, Jitka; Man, Petr; Pompach, Petr; Vohradsky, Jiri; Kovar, Jan (Molecular and cellular biochemistry, 2008)
We have shown previously that iron deprivation significantly stimulates the uptake of non-transferrin ferric iron from ferric citrate by erythroleukemia K562 cells and that this stimulation depends on protein synthesis. However, we have not detected increased expression of any known iron transport protein (Kovar J. et al. (2006) Blood Cells Mol Dis 37:95-99). Therefore, in order to identify membrane proteins of K562 cells with increased expression under iron deprivation, we employed the isolation of membrane proteins by two-phase partitioning system, protein separation by high-resolution 2D electrophoresis, computer differential analysis, and tandem mass spectrometry. Employing these techniques we identified two proteins with statistically significant upregulation, i.e., aldolase A (ALDA) and voltage-dependent anion channel 2 (VDAC2). The upregulation of aldolase A and VDAC2 in K562 cells under iron deprivation was also confirmed by western blot analysis. This is the first time when the control of aldolase A and VDAC2 levels by iron status of the cell is demonstrated.
Keywords: Gene Expression Regulation; aldolasa; Iron Deficiencies; K562 Cells; Fructose-Bisphosphate Aldolase; buňky K562; upregulace; Humans; deficit železa; lidé; Up-Regulation; Voltage-Dependent Anion Channel 2; napětím ovládaný aniontový kanál 2; regulace genové exprese